Foodpanda customer service support foodpanda Malaysia / Nur Hasyimah Abdul Khalil, Siti Hajar Ismail and Wan Syamin Izzati Wan Suhaimi - Abdul Khalil, Nur Hasyimah; Ismail, Siti Hajar; Wan Suhaimi, Wan Syamin Izzati (2017)
Foodpanda, a market leader in online food delivery for emerging markets. E-commerce moves fast, especially when it's on a motorbike in the form of a hot soup getting colder by the minute. Whatever the country, Foodpanda's customers are hungry and anxiously watching the clock.The online food ordering business is witnessing exponential growth. The organised food delivery is valued at $15 billion in Malaysia . Foodpanda entered the Malaysian market owing to its tremendous growth potential. The food retail market in Malaysia is expected to reach $894.98 billion by 2020 Also, the food industry market in Malaysia is expected to touch $1 trillion by 2020 and a significant portion of the market shall be occupied by the online food delivery services.